A systematic review of decision aids that facilitate elements of shared decision-making in chronic illnesses: a review protocol - Wieringa, Thomas H. (Syst Rev, 2017)
BACKGROUND: Shared decision-making (SDM) is a patient-centred approach in which clinicians and patients work side-by-side to decide together on the best course of action for each patient’s particular situation. Six key elements of SDM can be distinguished: situation diagnosis, choice awareness, option clarification, discussion of harms and benefits, deliberation of patient preferences and making the decision. Decision aids (DAs) are tools that facilitate SDM. The impact of DAs for chronic illnesses on SDM, clinical and patient reported outcomes remains uncertain. METHODS: We will perform a systematic review aiming to describe (a) which SDM elements are incorporated in DAs for adult patients with chronic conditions and (b) the effects of DA use on SDM, clinical and patient reported outcomes. This manuscript reports on the protocol for this systematic review. The following databases will be searched for relevant articles: PubMed, Embase, Web of Science, CINAHL and PsycINFO, from their inception to October 2016. We will ascertain ongoing research by querying experts and searching trial registries. To enhance feasibility, we will limit the review to randomized controlled trials (RCTs) including patients with chronic cardiovascular and/or respiratory diseases and/or diabetes. SDM elements incorporated in DAs, DA effects and DA itself will be described. DISCUSSION: This study will characterize DAs for chronic illness and will provide an overview of their effects on SDM, clinical and patient reported outcomes. We anticipate this review will bring to light knowledge gaps and inform further research into the design and use of DAs for patients with chronic conditions. SYSTEMATIC REVIEW REGISTRATION: PROSPERO registration number: CRD42016050320. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13643-017-0557-9) contains supplementary material, which is available to authorized users.